Variation in antioxidant potential of Vigna unguiculata grown in pure and amended soil - Zohaib Saeed; Shahid Iqbal; Umer Younas; Syed Majid Bukhari; Muhammad Pervaiz; Asma Zaidi (Kuwait Journal of Science)
The variation in antioxidant capacity on Vigna unguiculata was determined by carrying out the pot experiment in pure and in amended soil. After amending the soil, the suitability of sewage sludge for agricultural purposes was assessed. V. unguiculata was grown in six pots with different soil amendments including control soil, 20%, 40%, 60% and 80% sludge proportion as well as pure sludge. Antioxidant contents increased in linear fashion in all plant parts when grown in soil amendments possessing 20%, 40% and 60% sludge proportion; With 80% sludge proportion as well as in pure sludge, antioxidant contents decreased due to enhanced oxidative stress caused by higher concentrations of metal ions present with in the sewage sludge. Antioxidant potential assessed by DPPH assay, ABTS± scavenging activity and lipid peroxidation method showed significant improvement up to the soil amendments with 60% sludge proportion and decreased in higher amendments.